What is the best treatment for anemia in pregnant women in the third trimester: Ferric carboxymaltose or oral iron therapy? (Annals of Medical Research, 2023)
Aim: Iron deficiency anemia (IDA) is a significant health problem in pregnant women. We aimed to evaluate the effect of gestational IDA and to compare the results of iron therapy in pregnant women.Materials and Methods: This retrospective cohort study of pregnant women in the third trimester analyzed the records of 63 women not taking any iron supplements, 70 women receiving intravenous ferric carboxymaltose therapy (FCM), and 73 pregnant women receiving oral iron therapy. It compared maternal and neonatal outcomes of the three groups.Results: The mean age of the 206 pregnant women included in the study was 29.19±4.34 (19-44; min–max). Only 1% of anemic women received a blood transfusion in the postpartum period. There was no difference between the groups' mean age and gestational week. The median values of gravida and parity were the same in all 3 groups (Gravida=2, Parity=1). Maternal hemoglobin (Hb) value of the non-iron group was lower than that of the other groups (p
Keywords: Anemia; Ferric carboxymaltose injection; Iron deficiency anemia; Pregnancy; Taking iron supplements